2008
DOI: 10.1177/0003319707304533
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis Mimicking Acute Inferior Myocardial Infarction

Abstract: A 56-year-old man presented with acute pancreatitis and electrocardiographic abnormalities, suggesting acute inferior myocardial infarction. An emergent coronary angiogram showed normal coronary arteries. The clinical significance and therapeutic implications of this rare finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…ECG abnormalities have been frequently documented in patients with acute pancreatitis. The most common ECG changes consist of nonspecific repolarization abnormalities (1). Although documented, ST-segment elevation is rare (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…ECG abnormalities have been frequently documented in patients with acute pancreatitis. The most common ECG changes consist of nonspecific repolarization abnormalities (1). Although documented, ST-segment elevation is rare (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly encountered ECG findings in the studies performed in AP cases are changes in the ST-T interval (13,14,24,25). Repolarization changes in these studies were described to be "nonspecific".…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, electrocardiographic (ECG) findings were evaluated, and "nonspecific" repolarization was described to be the most common ECG finding detected among ST-T changes, and it was reported to be an unimportant finding (13,14). However, the clinical significance of this finding and influence on the prognosis was not evaluated sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…AP has frequently been reported to be associated with transient electrocardiographic (ECG) changes such as ST-T changes mimicking myocardial infarction, sinus bradycardia (5), repolarization changes (6), nonspecific T wave changes and accelerated atrial or nodal rhythms (7) have also been reported in early phase of acute pancreatitis. In addition, QT interval changes, particularly early repolarization was described to be the most common ECG finding of AP patients (8,9). QT dispersion was defined as an index of the spatial dispersion and attributed to difference of ventricular recovery times (10).…”
Section: Introductionmentioning
confidence: 99%